Perspektif Konsumen terhadap Pemasaran Paket MICE pada Departemen Pemasaran Hotel Aston Madiun - Priscila Triviana Dewi (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2019)
This study discusses the consumer perspective about the marketing activities of MICE packages organised by the Sales and Marketing Department at Aston Madiun Hotel and Conference Center. The component of organising marketing activities to be evaluated refers to the Marketing Mix model developed by Kotler (2014) knows as 4Ps (product, price, promotion, and place). In this study, researchers used quantitative and qualitative data. Data collection is done by distributing questionnaires to 112 respondents determined through purposive sampling, namely visitors who have purchased MICE packages at Aston Madiun Hotel and Conference Center. Data collection was also obtained from interviews with guests and the Sales and Marketing Department as organisers of hotel marketing activities, observation and literature. In order to formulate the overall evaluation steps, an analysis of the four sectors of hotel marketing activities was carried out in the form of analysis, planning, implementation, and evaluation whose results will be described descriptively. The results showed that the overall marketing mix component received a positive response from guests who had purchased the MICE package at the Aston Madiun Hotel. Two questionnaire items obtain quite low scores, namely hotel items routinely offer and update the details of MICE packages directly to companies and hotels utilising all print media for marketing MICE package activities. The data obtained from the study will be used as study material to evaluate the marketing activities of the Marketing Department in marketing an Aston Madiun Hotel service product, in the form of accuracy of analysis, product development that is in line with the main potential of the hotel, implementation of targeted market segmentation and always evaluating every marketing process that has been passed.